Appointment of forensic examinations in the course of investigation of criminal offences related to raiding - S. A. Tiulieniev (Law and Safety)
Establishment and development of the economic security of the state requires taking effective measures to counteract and minimise the negative impact of criminal offences that encroach on public relations in the areas of economic activity, legal activities of business entities, professional activities of public administration entities, etc. Among such criminal offences, much attention is paid to those with signs of raiding, i.e. those related to the unlawful takeover and seizure of property, assets of enterprises, institutions, organisations, corporate rights to them and other resources, encroachment on the rights of owners or authorised persons of business entities of various forms of ownership, etc. An important role in proving and clarifying the circumstances to be proved in these criminal offences is played by expert opinions. Given the insufficient elaboration of the issues related to the appointment of forensic examinations in the course of investigation of criminal offences related to raiding, the purpose of the article is to define the range of forensic examinations which are appointed during the pre-trial investigation of the latter, and to clarify the specifics of their appointment. To achieve this goal, the article uses a range of general scientific methods, as well as some philosophical and special research methods, in particular, analysis, synthesis, systemic and structural method, forecasting method and dialectical method.